2018
DOI: 10.1186/s12887-018-1088-9
|View full text |Cite
|
Sign up to set email alerts
|

Severe eye complications from toxic epidermal necrolysis following initiation of Nevirapine based HAART regimen in a child with HIV infection: a case from Cameroon

Abstract: BackgroundToxic epidermal necrolysis (TEN) is a rare life threatening dermatological disorder characterized by extensive epidermal detachment and erosion of mucous membranes. It is typically a side effect of some medications. Nevirapine, a nonnucleoside reverse transcriptase inhibitor (NNRTI) is one of the frequently used components of highly active antiretroviral therapy (HAART). Skin rash is its common adverse reaction, usually mild and rarely progressing to TEN. Ophthalmic involvement is common as well but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…TEN is characterized by severe cutaneous adverse reaction (SCAR) characterized by extensive detachment of the epidermis and mucous membranes, which could potentially lead to blindness in children (Thammakumpee et al 2013). However, the World Health Organization (WHO) recommends efavirenz and nevirapine as highly active antiretroviral therapy (HAART) for low-income countries due to their low cost, efficacy, and easy accessibility (Tchetnya et al 2018).…”
Section: Potential Effects On Humans and Aquatic Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…TEN is characterized by severe cutaneous adverse reaction (SCAR) characterized by extensive detachment of the epidermis and mucous membranes, which could potentially lead to blindness in children (Thammakumpee et al 2013). However, the World Health Organization (WHO) recommends efavirenz and nevirapine as highly active antiretroviral therapy (HAART) for low-income countries due to their low cost, efficacy, and easy accessibility (Tchetnya et al 2018).…”
Section: Potential Effects On Humans and Aquatic Speciesmentioning
confidence: 99%
“…Toxic epidermal necrolysis, or Lyell's syndrome, is a rare idiosyncratic life‐threatening side effect of nevirapine administered to infants diagnosed with HIV infection (Tchetnya et al 2018). Toxic epidermal necrolysis is characterized by severe cutaneous adverse reaction characterized by extensive detachment of the epidermis and mucous membranes, which could potentially lead to blindness in children (Thammakumpee and Yongsiri 2013).…”
Section: Potential Effects On Humans and Aquatic Speciesmentioning
confidence: 99%
“…This predominance was probably because a higher number of patients of this age group [87 (50%)] were admitted for HIV disease treatment during the study period. However, other studies (31)(32)(33) have reported a higher percentage of ADRs to HAART in geriatric and pediatric HIV-carrying populations.…”
Section: Discussionmentioning
confidence: 86%
“…3 We accessed nine reports of SJS/TEN in children exposed to NVP describing 29 patients in total. 6,7,8,9,10,11,12,13,14 Although NVP hypersensitivity has been associated with higher CD4 cell counts in adults (> 250 cells/μL in females and > 400 cells/μL in males), the above case reports show SJS and TEN occurring at any stage of immune suppression in paediatric populations. 8 It has been suggested that the paucity of cases reporting on the association between NVP in children and SJS/TEN may be a result of prescribing behaviour rather than an actual decreased risk compared with adults.…”
Section: Introductionmentioning
confidence: 88%